2004
DOI: 10.1007/s00234-003-1145-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI in herpes simplex encephalitis: a report of three cases

Abstract: Herpes simplex virus encephalitis (HSVE) is the most frequent fatal viral infection of the brain. Because antiviral treatment may improve the prognosis significantly, early diagnosis is mandatory. Imaging diagnosis rests on conventional MRI for the visualization of lesions in the limbic system, the hallmark of HSVE. Diffusion-weighted MRI (DW-MRI) has not been used for the evaluation of HSVE. We report on the DW-MRI findings in three patients with HSVE, who had cortical diffusion abnormalities in affected brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 7 publications
0
50
1
3
Order By: Relevance
“…Follow-up MR imaging examinations should be performed because they may show characteristic basal ganglia lesions in the later disease stage. 24 Isolated cortex involvement on DWI has been reported in other conditions, such as encephalitis, [25][26][27] hypoxia, 28 and epilepsy. [29][30][31][32] In these cases, further radiologic signs, such as cortical swelling, contrast enhancement on T1-weighted images, absence of hyperintensities on conventional images, predilection sites (hippocampus), and the partly observed resolution of the findings during the disease course may be useful discriminating factors from CJD.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up MR imaging examinations should be performed because they may show characteristic basal ganglia lesions in the later disease stage. 24 Isolated cortex involvement on DWI has been reported in other conditions, such as encephalitis, [25][26][27] hypoxia, 28 and epilepsy. [29][30][31][32] In these cases, further radiologic signs, such as cortical swelling, contrast enhancement on T1-weighted images, absence of hyperintensities on conventional images, predilection sites (hippocampus), and the partly observed resolution of the findings during the disease course may be useful discriminating factors from CJD.…”
Section: Discussionmentioning
confidence: 99%
“…McCabe et al [77] reported an adult with HSVE in whom HSV PCR was negative, but early diffusion restriction was observed in the anterior temporal lobes and the insular cortex. More reports demonstrating improved sensitivity of DWI over fluid-attenuated inversion recovery (FLAIR) sequences were soon to follow in adults [78], children [79], and neonates [80,81]. One report demonstrated correlation between DWI lesions and clinical response to treatment [82].…”
Section: Neuroimagingmentioning
confidence: 99%
“…Although, typically, there is corresponding T 2 hyperintensity, several studies have suggested that the diffusionweighted signal changes are more sensitive than those on conventional MR sequences [19,20]. Moreover, DWI may be more reliable than even polymerase chain reaction testing for the early diagnosis of herpes encephalitis [21].…”
Section: Infectious Viral Herpes Encephalitismentioning
confidence: 99%
“…Diffusion restriction is common in herpes encephalitis [19,20,22], but lesions that demonstrate T 2 shine-through have also been described [20,22]. Diffusion restriction may result from the glutamate excitotoxic pathway, as the concentration of glutamate in the cerebrospinal fluid increases significantly in the setting of herpes encephalitis [23].…”
Section: Infectious Viral Herpes Encephalitismentioning
confidence: 99%